Capitanias hereditárias: herança colonial sobre desigualdade e instituições - Innocentini, Thaís Cristina (2009)
This paper aims at identifying the effects of historical inequality in the Brazilian municipalities formation on the actual conditions of land and income inequalities and on institutions quality. In particular, we use, latitude, longitude and the foundation date of Capitanias Hereditárias as historical determinants for the actual institutions of Brazilian municipalities. Controlling for area, foundation year, Portugal distance, soil types, average rain, temperature altitude, and socio-economical variables, the results suggest that the main colonial heritage left from Capitanias Hereditárias is large land concentration. This empirical evidence seems to be robust to the inclusion of variables that capture Brazilian sugar cane and gold ciles and State-fixed effects. Moreover, we find ambiguous effect on Brazilian institutions.